Spatial modulation for multiple antennas wireless systems - Tan, Jiong Hao (Nanyang Technological University, 2021)
Multiple-Input-Multiple-Output (MIMO) systems is an extensive topic that has gain a lot of interest for comprehensive research in recent publications to cater to the rapid demand of present and future wireless communication systems. MIMO systems are thoroughly studied to constantly look for ways to improve and solve existing challenges. However, there are serious trade-offs and imperfections to MIMO systems. Disadvantages such as inter-channel interference, hardware complexity, cost, and power consumption exist in MIMO systems that need to be resolved. Hence, a new form of modulation technique, known as Spatial Modulation is recommended to resolve a few existing challenges of MIMO systems. Research has shown that by integrating Spatial Modulation into MIMO systems, cost and complexity can be lowered and yet still sustain a high data rate and large user capacity. Thus, this project focus on analysing the performance of Spatial Modulation over different channel conditions, a number of transmit- antennas, and power allocation methods. We simulate the basic modulation concepts with different channel conditions. Afterward, we evaluate a few receiver detection techniques and apply them to our SM-OFDM system. Our simulated experiments showed that the SM-OFDM system can prevent inter-channel interference, reduce receiver complexity and cost. Furthermore, our simulated results proved that the SM-OFDM system is reliable and can withstand various configurations of transmitting and receiving antennas making it ideal for various wireless communication systems.